Does AI Make Healthcare More Personalized? An Academic Review of Precision Medicine - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2022)
Does AI Make Healthcare More Personalized? An Academic Review of Precision Medicine The concept of personalized medicine—tailoring medical treatment to ...
Keywords: Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care; Precision Medicine